Simulation and Experimental Study on Dynamic Characteristic of Planetary Gear Transmission - Xiaolan Pang (Jixie chuandong)
In order to solve the problem of high failure rate in the operation of planetary power shift gearbox for engineering vehicles， a dynamics simulation model of planetary gearbox is established based on the dynamics transmission theory， and the rotational speed， torque and transmission efficiency of planetary transmission components are analyzed. The ADAMS and Matlab simulation software are used to establish the virtual prototype joint simulation model of the gearbox， the dynamic performance of the gearbox under the forward working condition of the vehicle is simulated， and the transmission efficiency and power flow direction of the planetary gearbox are analyzed. The test results show that the speed change of the gearbox before and after gear shifting is relatively gentle， which shows that the new dynamic gear shifting strategy can reduce the gear shifting time of the gearbox and improve the dynamic response of the gearbox effectively during the operation of the engineering vehicle. The research results have practical significance for condition monitoring and power shift strategy formulation of planetary gearbox.